Establishment of diagnostic reference levels in cardiac computed tomography. Issue 10 (30th August 2019) - Rawashdeh, Mohammad; Saade, Charbel; Zaitoun, Maha; Abdelrahman, Mostafa; Brennan, Patrick; Alewaidat, Haytham; McEntee, Mark F.
Abstract: The aim of this study was to determine diagnostic reference levels (DRLs) for cardiac computed tomography (CCT) in Jordan. Volume computed tomography dose index (CTDIvol ) and dose–length product (DLP) were collected from 228 CCTs performed at seven Jordanian hospitals specialized in cardiac CT. DRLs for cardiac CT were defined at the 75th percentile of CTDIvol and DLP. CTDIvol and DLP were collected from 30 successive cardiac CT in each center except for one center (18 scans). The 75th percentile of the CTDIvol and the DLP of the centers calculated from mixed retrospective and prospective gated modes were 47.74 milligray (mGy) and 1035 mGy/cm, respectively. This study demonstrated wide dose variations among the surveyed hospitals for cardiac CT scans; there was a 5.1‐fold difference between the highest and lowest median DLP with a range of 223.2–1146.7 mGy/cm. Differences were associated with variations in the mAs and kVp. This study confirmed large variability in CTDIvol and DLP for cardiac CT scans; variation was associated with acquisition protocols and highlights the need for dose optimization. DRLs are proposed for CCT; there remains substantial potential for optimization of cardiac CT examinations for adults in Jordan.